Mode I interlaminar fracture of carbon/epoxy multidirectional laminates - Pereira, A.B.
This paper reports an experimental study on the mode I interlaminar fracture of carbon/epoxy multidirectional specimens with 0degrees/thetadegrees delaminating interfaces. The suitability of the double cantilever beam (DCB) specimens was first evaluated in three-dimensional (3D) finite element (FE) analyses, which addressed possible elastic couplings associated problems. In the DCB tests, extensive fibre bridging occurred as a result of transverse cracking of theta-oriented plies. This complex damage morphology caused pronounced R-curves with artificially high final values of the critical strain energy release rate, G(1c). In these circumstances, G(1c) values of initiation from the film generated starter crack were considered the only true interlaminar properties. Moreover, they were found to be fairly independent of the delaminating interface, a result that could be interpreted in additional FE analyses concerning the interlaminar stress field ahead of the crack tip.